ICRISAT component, Kenya - Annual Technical Report 2022 - International Crops Research Institute for the Semi-Arid Tropics (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
ICRISAT team and partners implemented activities that were planned for 2022. Training materials have been developed as climate-relevant knowledge products, CIS decision support tools and bundled CSA packages. Pre-season and in-season agro-advisories were developed and broadcasted among more than 22,000 smallholder farmers to assist them with an on-farm decision- making. Thirty demonstration farms (of which 19 were led by female farmers) established following the screening on environmental and social safeguards. These demonstration plots tested the performance of drought-tolerant crops of sorghum (Gadam White), pearl millet (ICMV 88809), pigeonpea (Mbaazi3, Mbaazi 4, Mbaazi M1) and beans (Nyota KAD -02) under conservation agriculture as well as conventional tillage.